Seronegative Myasthenia Gravis, as a Rare Autoimmune Condition in Turner Syndrome - Rimah Sharief; Amir Miodovnik; Roja Motaghedi (Case Reports in Pediatrics)
Girls with Turner syndrome (TS), especially with isochromosome 46,X,i(X)(q10), are prone to develop autoimmunity. Associations of several autoimmune conditions with TS have been frequently described in the past. However, the unique combination of TS and myasthenia gravis (MG) has been reported only once before in a girl with mosaic monosomy 45,X/46,XX. Here, we present the second case of a girl affected with seronegative MG but with mosaic isochromosome TS. This is a child with developmental delay presented with muscle weakness, frequent fall, and bilateral ptosis. Diagnosis of MG was made based on positive Tensilon and electromyography tests and excellent response to intravenous immunoglobulin. At the age of 11 years due to short stature and developmental delay, a karyotype was done and revealed the mosaic isochromosome 45,X/46,X,i(X)(q10). Overall, clinicians should be aware of the vulnerability of girls with TS to autoimmunity, especially if the isochromosome 46,X,i(X)(q10) karyotype is identified. Furthermore, if a child with TS develops muscle weakness, ptosis, or ophthalmoplegia, MG should also be included in the differential diagnosis, particularly if other concurrent autoimmune conditions are present.